Evaluating Single‐Spacecraft Observations of Planetary Magnetotails With Simple Monte Carlo Simulations: 1. Spatial Distributions of the Neutral Line. Issue 12 (22nd December 2018) - Smith, A. W.; Jackman, C. M.; Frohmaier, C. M.; Coxon, J. C.; Slavin, J. A.; Fear, R. C.
Abstract: A simple Monte Carlo model is presented that considers the effects of spacecraft orbital sampling on the inferred distribution of magnetic flux ropes, generated through magnetic reconnection in the magnetotail current sheet. When generalized, the model allows the determination of the number of orbits required to constrain the underlying population of structures: It is able to quantify this as a function of the physical parameters of the structures (e.g., azimuthal extent and probability of generation). The model is shown adapted to the Hermean magnetotail, where the outputs are compared to the results of a recent survey. This comparison suggests that the center of Mercury's neutral line is located dawnward of midnight by 0 . 3 7 − 1 . 02 + 1 . 21 R M and that the flux ropes are most likely to be wide azimuthally (∼50% of the width of the Hermean tail). The downtail location of the neutral line is not self‐consistent or in agreement with previous (independent) studies unless dissipation terms are included planetward of the reconnection site; potential physical explanations are discussed. In the future the model could be adapted to other environments, for example, the dayside magnetopause or other planetary magnetotails. Key Points: Monte Carlo model allows the estimation of X‐line location and reconnection frequency given sampling with a single spacecraft Mercury's magnetotail reconnection site is consistent with a center offset ( 0 . 3 7 ‐ 1 . 02 + 1 . 21 R M ) dawnward of midnight Mercury's downtail X‐line location is only self‐consistent if dissipation terms are included planetward of the X‐line